Targeted therapy with histamine antagonists - New challenges to fight with breast cancer - Więsyk, Piotr Jan; Oleksa, Paulina; Chilimoniuk, Zuzanna; Dobosz, Maciej; Sobczyk, Maciej; Słaboń, Małgorzata (Journal of Education, Health and Sport, 2022)
Breast cancer (BC) is currently the most commonly diagnosed cancer in women. BC is most often derived from the epithelial tissue of the mammary gland and is a global problem due to the steady increase in morbidity and mortality in most countries. A particular problem today is the triple negative subtype (TNBC), which accounts for approximately 10-15% of breast cancer cases. BC occurs most frequently in young women and is characterised by various biological characteristics, an unfavourable clinical course and a poor prognosis. Recent studies to detect the effects of histamine receptors on breast cancer have shown that all H1R-H4R receptors are also hyperactive in the cancer microenvironment. Chronically maintaining a high level of histamine in the tumour-affected tissue contributes to increased angiogenesis at this site, induction of cancer cells proliferation and T lymphocyte dysfunction. The rising incidence of breast cancer is contributing to an increasing amount of research into targeted therapies. Studies on the effect of histamine antagonists through H1R-H4R receptors have proven their effectiveness in the treatment of breast cancer. Among those in the study, there was a reduction in tumour growth, cell proliferation and an increase in apoptosis. The use of histamine antagonists also contributed to a reduced risk of death from breast cancer and increased overall survival (OS). Therefore, targeted therapy is needed to improve the prognosis of patients with breast cancer.